Accounting Concepts in the Framework of Sharia Objectives Maqashid Sharia - H. Hersugondo (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
The primary objective of Maqashid Shariah is to promote the well-being of humanity and all living beings. This principle aligns closely with the field of accounting, especially considering that modern accounting often emphasizes materialistic values, which in turn reinforce capitalist ideologies. Capitalism tends to empower the strong while marginalizing the weak, leading to social and economic inequality. It is often viewed as inhumane due to its potential for exploitation—whether by individuals or by states over others. Therefore, there is a pressing need to reform accounting, beginning with its fundamental definition. Definitions are critical, as they shape perspectives and practices. This study adopts a qualitative approach within a postmodern paradigm, viewed through the lens of Maqashid Shariah, which encompasses three core categories: dharuriyyat (essentials), hajiyyat (complementary needs), and tahsiniyyat (enhancements). The aim of this research is to propose a new definition of accounting grounded in Maqashid Shariah principles. The result is a redefined concept of accounting: it is a science that provides both quantitative and qualitative information to stakeholders and shareholders about a company's operations and condition, free from manipulation, with the ultimate goal of fostering harmony across all aspects of life.